1983
DOI: 10.1128/aac.23.4.559
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of Bay 09867, a new quinoline derivative, compared with those of other antimicrobial agents

Abstract: The in vitro activity of Bay 09867, a new quinoline derivative, was compared with those of norfloxacin, nalidixic acid, ceftazidime, cefaclor, cefuroxime, gentamicin, and other antimicrobial agents, when appropriate, against 410 A new cluinoline derivative, 1-cyclopropyl-6-fluro-1, 4-dihydro-4-oxo-7-(1-piperazinyl)-3-quinolinecarboxylic acid hydrochloride (Bay 09867) (Fig. 1 Inocula were prepared in the following manner. For all strains except those of B. fragilis, streptococci (including pneumococci), N. go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
236
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 494 publications
(246 citation statements)
references
References 3 publications
9
236
1
Order By: Relevance
“…However, the half-life is considerably shorter in our patients (Table III) than in other studies where it was found to range between 3 and 5 hours (Wingender et al, 1984;Borner et al, 1986). High concentrations of ciproftoxacin were achieved in the urine and in most of the dosing interval by far exceeding the minimal concentrations necessary to inhibit growth of urinary tract pathogens (Wise et al, 1983;Fass, 1983). In a few of our patients the concentration towards the end of the interval was rather low and taking into account the relatively short half-life a twice daily schedule should be recommended for this dosage of ciproftoxacin.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…However, the half-life is considerably shorter in our patients (Table III) than in other studies where it was found to range between 3 and 5 hours (Wingender et al, 1984;Borner et al, 1986). High concentrations of ciproftoxacin were achieved in the urine and in most of the dosing interval by far exceeding the minimal concentrations necessary to inhibit growth of urinary tract pathogens (Wise et al, 1983;Fass, 1983). In a few of our patients the concentration towards the end of the interval was rather low and taking into account the relatively short half-life a twice daily schedule should be recommended for this dosage of ciproftoxacin.…”
Section: Discussioncontrasting
confidence: 60%
“…Cipro ftoxacin is a structural analogue of nalidixic acid and has very high in vitro activity against a wide variety of organisms including multiply resistant bacteria (Wise et al, 1983). The purpose of this investigation was therefore to evaluate the clinical and bacteriological efficacy of ciproftoxacin in SCL patients with urinary tract infection which were resistant to other peroral therapy.…”
mentioning
confidence: 99%
“…It is believed that the mode of action of this family of drugs is through binding DNA-gyrase enzyme 2 . It is also reported that there is a direct correlation of fluoroquinolone bonding with inhibition of DNA-gyrase enzyme activity and induction of DNA breakage.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies with these drugs in the therapy of Pseudomonas sp. infections are warranted.Pefloxacin and ciprofloxacin are two new quinoline carboxylic acid derivatives (12,15). Although structurally similar to nalidixic acid, the spectrum of activity of pefloxacin and ciprofloxacin includes Enterobacteriaceae, Pseudomonas sp., and many gram-positive cocci.…”
mentioning
confidence: 99%